2006
DOI: 10.1063/1.2194587
|View full text |Cite
|
Sign up to set email alerts
|

Miniature hybrid plasma focus extreme ultraviolet source driven by 10kA fast current pulse

Abstract: A miniature hybrid plasma focus device, operated in xenon gas medium and driven by a 10kA fast current pulse, has been used to generate extreme ultraviolet radiation in the range of 6–15nm. At present the radiation characteristics from xenon plasma were mainly assessed qualitatively using standard tools such as visible light framing camera, extreme ultraviolet (EUV) pinhole camera, and EUV photodiode. Strong pinching of xenon plasma is indicative from both visible and EUV imagings. The maximum size of the EUV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Even though the development of the theory of the Generalized Plasma Focus problem described above is seen to proceed logically from first principles, it is legitimate to inquire how its predictions compare with known experimental facts. Of particular importance is the following set of observations concerning near constancy of certain parameters, deduced [45][46][47][48][49] from a wide range of experiments [50][51][52][53][54][55][56][57][58][59][60][61] spanning the energy range from 0.1 J to 1 MJ: The existence of scaling laws that apply to a whole class of plasma focus devices is a reflection of the fact that the problem of solving the equations governing plasma dynamics can be decomposed into two weakly interdependent subproblems as discussed in Section II(A), the second of which is completely independent of all information pertaining to a device and is thus universally applicable to the whole class of devices. The important question is: why are these parameters constant?…”
Section: Comparison Of the Gpf Predictions With Experimentsmentioning
confidence: 99%
“…Even though the development of the theory of the Generalized Plasma Focus problem described above is seen to proceed logically from first principles, it is legitimate to inquire how its predictions compare with known experimental facts. Of particular importance is the following set of observations concerning near constancy of certain parameters, deduced [45][46][47][48][49] from a wide range of experiments [50][51][52][53][54][55][56][57][58][59][60][61] spanning the energy range from 0.1 J to 1 MJ: The existence of scaling laws that apply to a whole class of plasma focus devices is a reflection of the fact that the problem of solving the equations governing plasma dynamics can be decomposed into two weakly interdependent subproblems as discussed in Section II(A), the second of which is completely independent of all information pertaining to a device and is thus universally applicable to the whole class of devices. The important question is: why are these parameters constant?…”
Section: Comparison Of the Gpf Predictions With Experimentsmentioning
confidence: 99%
“…The wavelength of 13.5nm was chosen because it was found that Mo/Si multilayer mirrors could be fabricated with very high reflectivity (~70%) at this wavelength and stable in time [5][6][7][8]. Many of the sources under consideration use radiation from multicharged xenon ions [9,10] excited by a large number of sources like: the laser produced plasma [11,12], the synchrotron wiggler, Z-pinch [13], plasma focus [14] and capillary discharge produced plasma [9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…More than three decades of research on plasma focus (PF) devices, ranging from low to high energies, has introduced this device as a cost-effective and simple source of intensive ion and electron beams (Stygar et al 1982;Kelly and Marquez 1995;Wong et al 2002;Patran et al 2005;Mohanty et al 2007), soft and hard X-rays (Rawat et al 2004;Wong et al 2004;Neog et al 2006Neog et al , 2008 as well as neutron beams (Verma et al 2008). Due to a wide range of applications of high-energy, short-pulse electron beams in industry and medical sciences, such as lithography, micro-lithography, microscopy (Neff et al 1989;Lee et al 1997;Mohanty et al 2006), sterilization (Kotov and Sokovnin 2000), and deposition of various thin films (Zhang et al 2005), studies have been undertaken to characterize the electron beam emission and its energy spectrum in dense PF devices. The produced X-ray radiation by the interaction of electrons with anode tip has been used indirectly to measure electron beam energy spectrum.…”
Section: Introductionmentioning
confidence: 99%